Depression Care Management: Can Employers Purchase Improved Outcomes?. (8th June 2011) - Rost, Kathryn; Marshall, Donna; Shearer, Benjamin; Dietrich, Allen J.
Abstract : Fourteen vendors are currently selling depression care management products to US employers after randomized trials demonstrate improved work outcomes. The research team interviewed 10 (71.4%) of these vendors to compare their products to four key components of interventions demonstrated to improve work outcomes. Five of 10 depression products incorporate all four key components, three of which are sold by health maintenance organizations (HMOs); however, HMOs did not deliver these components at the recommended intensity and/or duration. Only one product delivered by a disease management company delivered all four components of care at the recommended intensity and duration. This "voltage drop, " which we anticipate will increase with product implementation, suggests that every delivery system should carefully evaluate the design of its depression product before implementation for its capacity to deliver evidence-based care, repeating these evaluations as new evidence emerges.